The Professional EFL Teacher: A Qualitative Exploration of Iranian University Lecturers’ Attitudes toward EFL Teacher Professionalism - Shiva Azizpour; Mohammad Hashamdar (Research in English Language Pedagogy, 2023)
This qualitative study explored Iranian university lecturers’ attitudes toward EFL teacher professionalism. Based on a researcher-developed protocol, semi-structured interviews were conducted with 14 university lecturers from State and Islamic Azad universities of Tehran, Karaj, Urmia, and Tabriz, Iran, whose teaching experiences ranged from 6 to 19 years, to delve into their attitudes and experiences toward EFL teacher professionalism. The interviews drew upon emergent methodology to categorize the interviewees’ value-laden comments into five major attitudinal themes of the meaning of EFL teacher professionalism,  the characteristics, requirements, and responsibilities of a professional EFL teacher, establishing rapport and positive relationship with students, colleagues, and administrative staff in a professional EFL teaching context, resolving possible organizational conflicts in a professional EFL teaching context, and the role of ethics in EFL teacher professionalism. The findings illustrated that professional university lecturers are expected to establish authority and certain relationship boundaries with students and maintaining these boundaries will keep professor-student relationships purely professional. Further, adhering to professional standards and ethics, preventing discrimination in the classroom, developing classroom management skills, fostering student autonomy, giving constructive feedback, and developing mutual respect, politeness, and trust might create a favorable environment as well as increased productivity at work. Besides, educational stakeholders and policymakers are expected to design certain guidelines and allocate the resources required to help university lecturers develop as professionals.